2021
DOI: 10.1038/s41598-021-94816-y
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic acid promotes hair growth in mice

Abstract: Glutamic acid is the main excitatory neurotransmitter acting both in the brain and in peripheral tissues. Abnormal distribution of glutamic acid receptors occurs in skin hyperproliferative conditions such as psoriasis and skin regeneration; however, the biological function of glutamic acid in the skin remains unclear. Using ex vivo, in vivo and in silico approaches, we showed that exogenous glutamic acid promotes hair growth and keratinocyte proliferation. Topical application of glutamic acid decreased the exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…In the present study, histidylphenylalanine levels were elevated in psoriatic lesions, but it has not been reported to be involved in pathogenetic mechanisms of psoriasis, and therefore remains to be further investigated. The increased levels of 2‐methylcitric acid in psoriatic lesions may be relate to the increased glutamate, which can promote keratinocyte proliferation 15 . 2‐methylcitric acid can inhibit glutamate dehydrogenase activity or glutamate transport through mitochondrial membrane to decrease glutamate oxidative metabolism, resulting in elevated glutamate 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, histidylphenylalanine levels were elevated in psoriatic lesions, but it has not been reported to be involved in pathogenetic mechanisms of psoriasis, and therefore remains to be further investigated. The increased levels of 2‐methylcitric acid in psoriatic lesions may be relate to the increased glutamate, which can promote keratinocyte proliferation 15 . 2‐methylcitric acid can inhibit glutamate dehydrogenase activity or glutamate transport through mitochondrial membrane to decrease glutamate oxidative metabolism, resulting in elevated glutamate 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of 2-methylcitric acid in psoriatic lesions may be relate to the increased glutamate, which can promote keratinocyte proliferation. 15 2-methylcitric acid can inhibit glutamate dehydrogenase activity or glutamate transport through mitochondrial membrane to decrease glutamate oxidative metabolism, resulting in elevated glutamate. 16 Dutkiewicz et al showed that glutamate levels were increased in psoriatic lesions compared with non-lesions and healthy controls.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Glutamic acid has an important role in hair growth and the proliferation of HF cells as an essential nutrient for DP and hair matrix cells. [ 33 , 34 , 35 ] N -acetyl aspartate is an important source of amino acids and acetates in the mammalian brain [ 36 ], and it is synthesized from aspartate and acetyl coenzyme A (acetyl-CoA) by the enzyme l -aspartate- N -acetyltransferase [ 37 ]. Acetyl-CoA is an important intermediate metabolite that is the hub of sugar, lipid, and protein metabolism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…KRT4 upregulation suggests significant increase in cell proliferation to promote SHF development and also increase cashmere yield [60]. Elevated expression of SLC1A2 suggests that it may promote hair growth and keratinocyte proliferation [61]. Dysregulation of LOC102190037/ LOC102179090/LOC102173866 may impair the essential role of lipid metabolism in goat skin functions, probably because lack of essential fatty acids could reduce water repulsion and increase trans-epidermal water loss [62].…”
Section: Discussionmentioning
confidence: 99%